A Literary Review On Potential Health Risks Of “Soft Drinks” (Journal of Namibian Studies : History Politics Culture, 2023)
Soft Drinks are carbonated water, sugar, and flavoring. Non-alcoholic beverages have less than 0.5% alcohol. Caffeine, coloring, and preservatives are also possible. Millions prefer soft drinks over water. In the 17th century, the first Western soft drinks were honey-sweetened water and lemon juice. Soft drinks are nutrient-free. Soft drinks mostly include filtered water and white sugar. In 2009, Sri Lankans consumed 62 million liters of carbonated soft drinks, and 82% of the population drank sugar-sweetened soft drinks, according to a 2012 survey. Soft drink intake is connected to obesity, diabetes, bone loss, osteoporosis risk, high blood pressure, acid reflux, metabolic syndrome risk, liver damage, digestive issues, dehydration, asthma, and aggressive behavior. This literature review investigated soft drink health impacts. The World Health Organization, scientific papers, and the internet provided soft drink hazard information. Thus, soft drink use endangers future generations.